Synergistic Antitumor Effects of Novel HDAC Inhibitors and Paclitaxel In Vitro and In Vivo - Zuco, Valentina (Public Library of Science, 2011)
Preclinical studies support the therapeutic potential of histone deacetylases inhibitors (HDACi) in combination with taxanes. The efficacy of combination has been mainly ascribed to a cooperative effect on microtubule stabilization following tubulin acetylation. In the present study we investigated the effect of paclitaxel in combination with two novel HDACi, ST2782 or ST3595, able to induce p53 and tubulin hyperacetylation. A synergistic effect of the paclitaxel/ST2782 (or ST3595) combination was found in wild-type p53 ovarian carcinoma cells, but not in a p53 mutant subline, in spite of a marked tubulin acetylation. Such a synergistic interaction was confirmed in additional human solid tumor cell lines harboring wild-type p53 but not in those expressing mutant or null p53. In addition, a synergistic cytotoxic effect was found when ST2782 was combined with the depolymerising agent vinorelbine. In contrast to SAHA, which was substantially less effective in sensitizing cells to paclitaxel-induced apoptosis, ST2782 prevented up-regulation of p21(WAF1/Cip1) by paclitaxel, which has a protective role in response to taxanes, and caused p53 down-regulation, acetylation and mitochondrial localization of acetylated p53. The synergistic antitumor effects of the paclitaxel/ST3595 combination were confirmed in two tumor xenograft models. Our results support the relevance of p53 modulation as a major determinant of the synergistic interaction observed between paclitaxel and novel HDACi and emphasize the therapeutic interest of this combination.